ACP-EU Trade Issues in the Agricultural and Fisheries Sectors: Agritrade Compendium 2013 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2013)
The present publication is a compendium of briefings published on the CTA Agritrade web site in 2013. The issues are addressed in a factual and non-partisan manner.